Participatory design in sensitive contexts: A proposal for a conceptual framework. (30th August 2022) - Raman, Sneha; French, Tara
Abstract: There has been an increasing focus on Participatory Design (PD) and design research involving 'vulnerable groups' and sensitive topics in recent years. Existing approaches, however, focus on working with discrete ' vulnerable groups' and/or sensitive topics, with limited work capturing shared learnings and key principles across these. In this position paper, we discuss our work specifically focusing on enabling participation from people perceived as vulnerable to engage on sensitive research topics, sharing key themes from project examples across three different contexts. We present a proposal for a conceptual framework synthesising key principles for Participatory Design in Sensitive Contexts. The framework emphasises: valuing lived experience as expertise; rights-based ethos foregrounding the political, ethical and social commitment of PD; asset-based design promoting individual and collective agency, voice and empowerment; and attuning participation with a focus on relationships, dynamics of engagement and wellbeing, to create appropriate conditions for genuine participation and transformation.